Decrease in Methoprene tolerant and Taiman expression reduces juvenile hormone effects and enhances the levels of juvenile hormone circulating in males of the linden bug Pyrrhocoris apterus. (October 2016) - Hejnikova, Marketa; Paroulek, Michal; Hodkova, Magdalena
Graphical abstract: Highlights: Met and Tai genes are required for JH stimulation of synthesis of proteins in accessory glands. Met and Tai genes are required for JH inhibition of synthesis of hexamerins in fat body. Met, but not Tai gene, is required for shortening of lifespan. Chemical composition of JH was identified as JH III skipped bisepoxide (JHSB3 ). Paradoxically, knockdown of Met and Tai increases the titer of JH, but inhibits its function. Abstract: Juvenile hormone (JH) produced by the corpus allatum (CA) stimulates vitellogenesis and reduces the synthesis of hexamerin proteins in adult females of Pyrrhocoris apterus . At present it is unknown whether the signaling pathway involving the JH receptor gene Methoprene tolerant (Met) and its binding partner Taiman (Tai), regulates the synthesis of accessory gland proteins (ACPs) and hexamerin proteins or effects male survival. Knockdown of genes by injecting Met dsRNA or Tai dsRNA, reduced the amount of ACPs whilst enhancing the amount of hexamerin mRNA in the fat body and the release of hexamerin proteins into haemolymph, as occurs after the ablation of CA. Lifespan was enhanced by injecting Met but not Tai dsRNA. Diapause associated with the natural absence of JH had a stronger effect on all these parameters than the ablation of CA or the knockdown of genes. This indicates there is an additional regulating agent. Both Met and Tai dsRNA induced a several fold increase in JH (JH III skiped bisepoxide) but a concurrent loss of Met or Tai disabled its function. This supports the view that the Met/Tai complex functions as a JH receptor in the regulation of ACPs and hexamerins.